2012
DOI: 10.29019/tsafiqui.v0i3.224
|View full text |Cite
|
Sign up to set email alerts
|

Manejo De La Nutrición Del Cultivo De Cacao en La Región De Santo Domingo

Abstract: Se diseñó un estudio a largo plazo para evaluar el efecto del manejo nutricional sobre el comportamiento morfoproductivo de dos cultivares de cacao (Theobroma cacao) desde la siembra hasta cuando el huerto estabiliza la producción. El estudio se inició en marzo del año 2009, en este artículo se reportan los datos obtenidos en dos años de establecimiento de la huerta experimental. El sitio está ubicado en la Granja Experimental de la Universidad Tecnológica Equinoccial, Extensión Santo Domingo. Se sembraron 1 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although the results, in general, are relatively higher than those of Castro (2015) in in the Santa Rosita estate in Irazola-Padre Abad, he found the almond yield of 607.61 kg /ha; Also, they are higher than the average yields for our country, 720 kg/ha and above the world average of 485 kg/ha (MINAGRI, 2018). How to explain this high yield in almonds, according to Recalde et al (2012) the clone CCN51 develops the sink of nutrients and other compounds early in the growth cycle, which ensures higher yields, because, in the second year of production with chicken manure, it found 428 kg/ha, in our case the evaluated plot is in its third year of production, which would explain the higher performance found. Organic production or combined with chemistry is a viable alternative, our result shows it, there are no statistical differences and the references contrast this behaviour; In this regard, Huera (2018) applying Full cocoa (organic + chemical) presented dry almond yields of 2 727.45 kg/ha and 1982.05 kg/ha for bio compost; Also, Gómez (2017) found yields of 1350 kg/ha for chemical fertilization and 1270 kg/ha for organic fertilization; Montes (2016) with diatomic phosphorus + ammonium sulfate (30+40 k/ha), obtained 1539 kg/ha; Álvarez et al (2015) found similar responses between chemical and organic treatments, with averages of 2730 kg/ha for conventional and 2521.43 for organic, and Ludeña (2015) in Jaén found yields of 1298.3 kg/ha with organic treatment.…”
Section: Performance Indicatorsmentioning
confidence: 83%
“…Although the results, in general, are relatively higher than those of Castro (2015) in in the Santa Rosita estate in Irazola-Padre Abad, he found the almond yield of 607.61 kg /ha; Also, they are higher than the average yields for our country, 720 kg/ha and above the world average of 485 kg/ha (MINAGRI, 2018). How to explain this high yield in almonds, according to Recalde et al (2012) the clone CCN51 develops the sink of nutrients and other compounds early in the growth cycle, which ensures higher yields, because, in the second year of production with chicken manure, it found 428 kg/ha, in our case the evaluated plot is in its third year of production, which would explain the higher performance found. Organic production or combined with chemistry is a viable alternative, our result shows it, there are no statistical differences and the references contrast this behaviour; In this regard, Huera (2018) applying Full cocoa (organic + chemical) presented dry almond yields of 2 727.45 kg/ha and 1982.05 kg/ha for bio compost; Also, Gómez (2017) found yields of 1350 kg/ha for chemical fertilization and 1270 kg/ha for organic fertilization; Montes (2016) with diatomic phosphorus + ammonium sulfate (30+40 k/ha), obtained 1539 kg/ha; Álvarez et al (2015) found similar responses between chemical and organic treatments, with averages of 2730 kg/ha for conventional and 2521.43 for organic, and Ludeña (2015) in Jaén found yields of 1298.3 kg/ha with organic treatment.…”
Section: Performance Indicatorsmentioning
confidence: 83%
“…Uribe et al (1998) observed a high response to nitrogen and potassium fertilization, while Mora et al (2011) reported an increase in yield with different doses of fertilization. Regarding Ecuador, Recalde et al (2012) showed that the influence of fertilization on yield is evident. However, establishing optimal nutritional management requires efficient use of nutrients, as suggested by Romero et al (2016), since fertilizing with more nutrients does not guarantee a higher yield (Puentes et al 2014a).…”
mentioning
confidence: 99%
“…In Ecuador, despite research on cacao nutrition is scarce, Carrillo et al (2010) reported that balanced fertilization has benefits on the physiology and architecture of the plant. Recalde et al (2012) stated the beneficial effect of fertilization on the crop. Amores et al (2010) reported that the beginning of the productive stage of the crop requires 212, 23, and 321 kg ha -1 of nitrogen, phosphorus, and potassium, respectively; as well as 140, 71, 7.1, and 0.9 kg ha -1 of calcium, magnesium, manganese, and zinc, respectively.…”
mentioning
confidence: 99%